Development of a nano biosensor for anti-gliadin detection for Celiac disease based on suspension microarrays. (24th August 2020) - Kharati, Maryam; Rabiee, Mohammad; Rostami-Nejad, Mohammad; Aghamohammadi, Elham; Asadzadeh-Aghdaei, Hamid; Zali, Mohammad Reza; Rabiee, Navid; Fatahi, Yousef; Bagherzadeh, Mojtaba; Webster, Thomas J
Abstract: Celiac disease is an autoimmune disorder represented by the ingestion of the gluten protein usually found in wheat, barley and rye. To date, ELISA has been the most accurate method for determining the presence of anti-gliadin, which is cumbersome, expensive (compared to a suspension microarray technique), and requires extensive sample preparation. In this study, in order to establish a more accurate assay to identify gliadin at lower concentrations, optical nano biosensors using an indirect immunoassay method for gliadin detection was designed and fabricated. For this, polycaprolactone (PCL) nano- to micro-beads were fabricated as a platform for the gliadin antigen which were optimized and nano functionalized with amine groups for such purposes. The gliadin antibody, which is selective to gliadin, was then added to the beads. Static light scattering tests were conducted to determine PCL particle size distribution and sizes were found from 0.1 to 30 μ m, which is suitable for flowcytometry detection devices. Anti-gliadin detection was performed using an anti IgG mouse antibody conjugated with FITC in a flow cytometry device to detect the smallest particle. Fluorescence intensity was investigated at different concentrations of anti-gliadin and a standard curve used to determine gluten concentration based on fluorescence intensity. Results showed that the fluorescence intensity increased with greater concentrations of anti-gliadin providing a very effective method of detection due to selectivity at a 5 ppm detection limit. This represents a new highly sensitive and fast method for anti-gliadin detection. Further, the disuse of a cross linker and the use of a dedicated antibody at a very low level (1 μ l) made this new method very economical to identify anti-gliadin concentrations at the nano level. In summary, this study provides a new, more accurate and sensitive, as well as less expensive system to detect anti-gliadin for the improved diagnosis of celiac disease.